EU Climate Leadership: Contradictions Inherent in Carbon Regulation - I. V. Bolgova; E. A. Stolyarova (Международная аналитика, 2024)
The article analyzes the EU Carbon Border Adjustment mechanism (CBAM) through the lens of the EU’s aspiration to strengthen its leadership in fighting climate change. The introduction of CBAM is viewed as another step toward achieving the EU's goal of climate neutrality, which has become a standard for global development. By studying the internal and external dynamics of CBAM's implementation, the article aims to analyze its role as a tool for diplomatic and exemplary leadership. On the one hand, the EU seeks to protect European producers from producers from countries with lower climate standards. On the other hand, the EU’s desire to involve other countries in creating CBAM-style mechanisms is supposed to strengthen the EU’s leadership, contributing to the formation of multilateral “climate clubs” and the gradual revision of the existing climate regime. However, the article suggests that there are inherent contradictions in the EU's approach. While it seeks to protect its economy through CBAM, it also frames these measures within the narrative of multilateral cooperation. This dual approach poses challenges to the EU's leadership potential. The protectionist nature of CBAM makes other global players, primarily the U.S., follow the same path of taking protective measures. China is not willing to give up its own framing of the climate agenda due to its importance for the construction of China’s international identity. Russia’s perception of the climate change problem is infl uenced by its national interests and the structure of economy. The projection of regulatory power beyond the EU’s borders also provokes resistance from developing and least developed countries, which can seriously damage the EU’s role as a normative power.